Biomed central part of Springer Nature [electronic resource] (DOAJ, 2020)
BioMed Central is an independent publishing house committed to providing immediate open access to peer-reviewed biomedical research. BioMed Central contains 184 journals (Dec 1, 2007). Many are citation-tracked and already have Impact Factors.